Developmental Regulation of Monoterpene Biosynthesis in the Glandular Trichomes of Peppermint - McConkey, Marie E. (American Society of Plant Physiologists, 2000)
Monoterpene production in peppermint (Mentha × piperita L.) glandular trichomes is determined by the rate of biosynthesis, as determined by (14)CO(2) incorporation, and is restricted to leaves 12 to 20 d of age. Using oil glands isolated from peppermint leaves of different ages, in vitro assay of the eight sequential enzymes responsible for the biosynthesis of the principal monoterpene (−)-menthol indicated that all but one biosynthetic enzyme had a very similar developmental profile. Activities were highest in leaves 12 to 20 d of age, with a sharp peak centered at 15 d. The exception, (−)-menthone reductase, the last enzyme of the pathway, exhibited a later peak of activity, which was centered at approximately 21 d. The correlation between in vitro enzyme activity and the rate of biosynthesis measured in vivo suggests that monoterpene formation is controlled mainly by the coordinately regulated activity of the relevant biosynthetic enzymes. Developmental immunoblotting of limonene synthase, which catalyzes the committed step of the pathway, demonstrated a direct correlation between enzyme activity and enzyme protein, suggesting that the dynamic time course for the remaining pathway enzyme activities also reflects the corresponding protein levels. RNA-blot analyses indicated that the genes encoding enzymes of the early pathway steps are transcriptionally activated in a coordinated fashion, with a time course superimposible with activity measurements and immunoblot data. These results demonstrating coincidental temporal changes in enzyme activities, enzyme protein level, and steady-state transcript abundances indicate that most of the monoterpene biosynthetic enzymes in peppermint are developmentally regulated at the level of gene expression.